KEABSAHAN PERKAWINAN SUKU DAYAK TUNJUNG DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Nomita Santi (Universitas 17 Agustus 1945 Samarinda, 2019)
AbstractThe validity of marriage based on article 2 paragraph (1) and paragraph (2) of marriage law, marriage is legal if it is carried out according to the laws of each religion and its beliefs and is recorded according to the applicable laws and regulations. Article 2 paragraph (1) and paragraph (2) of marriage law. But in the case of recording, there are still married couples whose marriages are not recorded in the registry office. The method of research conducted by the author is empirical juried. Data collection is done by the Longgang Amer area, Longgang Bigung District, and at the Presidium Office of the West Kutai regency customary council. The first conclusion, that the implementation of the traditional Tunjung Dayak Tribe marriage is lawful according to state law has fulfilled the provisions contained in law number 1 of 1974 article 2 paragraph (1) and paragraph (2). In the case of marriage registration, there is a spouse the wife whose marriage was not recorded in the registry office. This unregistered marriage caused the husband and wife and children born to not get legal protection. Second, the role and responsibility of the customary chief are to carry out a whole series of arrangements for the approval of prospective brides and grooms, and the three factors driving the occurrence of customary marriage in the Longgang Amer region are indigenous and customary laws are adhered to as invite for the Tunjung Dayak Tribe community.